Fumonisin B1 Induces Immunotoxicity and Apoptosis of Chicken Splenic Lymphocytes - Zhu, Fenghua; Wang, Yang (Frontiers in Veterinary Science, 2022)
Fumonisin B1 (FB1), produced by Fusarium, is among the most abundant and toxic mycotoxin contaminations in feed, causing damages to the health of livestock. However, the mechanisms of FB1 toxicity in chickens are less understood. As splenic lymphocytes play important roles in the immune system, the aim of this study was to investigate the immunotoxic effects and mechanisms of FB1 on chicken splenic lymphocytes. In the present study, the chicken primary splenic lymphocytes were harvested and treated with 0, 2.5, 5, 10, 20 and 40 µg/mL FB1. Then, the cell proliferation, damage, ultrastructure, inflammation and apoptosis were evaluated. Results showed that the proliferation rate and the activity of lactate dehydrogenase (LDH) was decreased by FB1 treatments. Consistently, the ultrastructure of splenic lymphocytes showed that FB1 at all the tested concentrations caused cell structure alterations, including nuclear vacuolation, mitochondrial swelling and mitochondrial crest fracture. Immunosuppressive effects of FB1 were observed by the decreased concentrations of interleukin-2 (IL-2), IL-4, IL-12 and interferon-γ (IFN-γ) in the cell culture supernatant. Furthermore, apoptosis was observed in FB1-treated cells by flow cytometry. The mRNA expressions of apoptosis-related genes showed that the expression of Bcl-2 was decreased, while the expressions of the P53, Bax, Bak-1 and Caspase-3 were increased with FB1 treatment. Similar results were found in the concentrations of apoptosis-related proteins in the cell supernatant by ELISA assay. Moreover, regression analysis indicated that increasing FB1 concentration increased LDH activity, concentrations of Bax, Bak-1 and mRNA expression of Bak-1 linearly, increased M1 area percentage quadratically, decreased concentration of IFN-γ, mRNA expression of Bcl-2 linearly, and decreased concentrations of IL-2 and IL-4 quadratically. Besides, regression analysis also showed reciprocal relationships between IL-12 concentration, Caspase-3 mRNA expression and increasing FB1 concentration. The increasing FB1 concentration could decrease IL-12 concentration and increase Caspase-3 mRNA expression. Altogether, this study reported that FB1 induced the immunotoxicity of chicken splenic lymphocytes and caused splenic lymphocytes apoptosis by the Bcl-2 family-mediated mitochondrial pathway of caspase activation.